An Answer to the "Crisis of Medicine"? The Modern Constitution Theory in Crisis Discourse 1925-1933 - Metzger, Nadine (Gesnerus, 2019)
Discussing the alleged crisis of medicine (ca. 1925-33) German physicians addressed the underlying mindset of medical theory and practice. Identified as oscientific crisis, they called the scientific epistemology of medicine into question. Since 1911 modern constitutional medicine had offered concepts potentially useful to overcome this crisis. Besides similar topics the two discussions shared prominent voices, presenting their ideas for better medicine in both discourses. However, this paper shows the minor role constitutional medicine actually played in the crisis discussion. It was rarely put forward as a solution to the supposed crisis and is conspicuously often discovered in discussions of historical background. Far more often, concepts designed to overcome constitutional medicine are invoked as a potential crisis solution, first and foremost the so-called constitutional therapy fathered by Vienna gynaecologist Bernhard Aschner which evokes pre-modern humoral pathology.
CRIS-Team WoS Importer:2019-08-30

Der Internist, Konstitutionspathologe und Sportmediziner Hermann Rautmann (1885–1956) - Metzger, Nadine (Sudhoffs Archiv; Zeitschrift für Wissenschaftsgeschichte, 2020)
In the 1920s, Freiburg internist Hermann Rautmann (1885–1956) contributed heavily to the then flourishing fields of constitutional medicine and sports medicine, being a notable figure in early medical statistics and heading the first university institute for sports medicine. However, in 1929 Rautmann left academic medicine in favour of a permanent position at Brunswick municipal hospital where he spent the rest of his professional life. Even so Rautmann’s promising university career was thus cut short he quickly regained his feet and established new ties to intellectually stimulating and professionally satisfying domains, e. g. aviation medicine, the Technical College Brunswick, and the Brunswick Academic Society. This article presents the first biography of this versatile medical scientist, including his ambivalent nazi years and rebuilding post-war activities – beyond university.
CRIS-Team Scopus Importer:2024-12-16
Keywords: academic career; Brunswick; constitutional medicine; medical statistics; physicians under nazism; sports medicine

Eine Antwort auf die «Krise der Medizin»? Die Moderne Konstitutionslehre im Krisendiskurs 1925 bis 1933 - Metzger, Nadine (Gesnerus, 2019)
Discussing the alleged «crisis of medicine» (ca. 1925–33) German physicians addressed the underlying mindset of medical theory and practice. Identified as «scientific crisis», they called the scientific epistemology of medicine into question. Since 1911 modern constitutional medicine had offered concepts potentially useful to overcome this «crisis». Besides similar topics the two discussions shared prominent voices, presenting their ideas for better medicine in both discourses. However, this paper shows the minor role constitutional medicine actually played in the «crisis» discussion. It was rarely put forward as a solution to the supposed «crisis» and is conspicuously often discovered in discussions of historical background. Far more often, concepts designed to overcome constitutional medicine are invoked as a potential crisis solution, first and foremost the so-called «constitutional therapy» fathered by Vienna gynaecologist Bernhard Aschner which evokes pre-modern humoral pathology.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Bernhard Aschner; Constitutional medicine; Crisis of medicine; Holism; Medical epistemology

Krankheit als Werturteil. Eine kleine Geschichte des Umgangs mit Krankheit und Kranken - Dross, Fritz; Metzger, Nadine (Aus Politik und Zeitgeschichte, 2018)

Kynanthropy: canine madness in Byzantine late antiquity - Metzger, Nadine (History of Psychiatry, 2015)
Those afflicted bark like dogs, scramble on all fours and loiter around graveyards - canine madness, referred to as kynanthropy, was an illness concept in its own right in the medicine of late antiquity. At roughly the same time as the medical description produced by Aëtius of Amida, the Syrian chronicler John of Ephesus, also from Amida, reported an epidemic of dog-like madness sweeping his home town in ad 560. The symptoms are identical and both authors are from Amida - what is the connection between the two depictions? In addition to the history of the medical concept, the example of the canine madness of Amida and its cultural embedding allows us to contextualize and interpret the significance of dog-like behaviour for the people of the sixth century AD.
EVALuna2:5618

Pathologische Menschenflucht. Melancholische misanthropia in der kaiserzeitlichen und frühbyzantinischen Medizin - Metzger, Nadine (Being Alone in Antiquity, 2021)
CRIS-Team Scopus Importer:2024-12-16

Poisoning, Ergotism, Mass Psychosis. Writing a History of Ancient Epidemics Beyond Infectious Diseases - Metzger, Nadine (Historical Social Research-Historische Sozialforschung, 2021)
"Vergiftung, Ergotismus und Massenpsychose. Antike Seuchengeschichte jenseits von Infektionskrankheiten". For the last 100 years, the modern concept of epidemics as contagious diseases caused by pathogenic agents or microorganisms entering the body has not only dominated present thinking about epidemics but highly influenced historiographical study of past disease as well. In the case of Greek and Roman antiquity, this led to extensive and thorough scholarly work on epidemics fitting the pattern of infectious diseases while incompatible cases were put aside notwithstanding that by ancient definition they were epidemics of the same quality: illness that affects many individuals of the same community at the same time. This includes cases retrospectively explained as mass poisoning, ergotism, and mass hysteria. This article discusses the methodological problem of disparate definitions of modern and ancient epidemics and argues for broadening the source base in the study of ancient epidemics to include accounts of diseases that do not fit into the modern mould of infectious disease. To demonstrate the benefit of this suggestion, two disregarded later ancient epidemics drawn from relatively unknown patristic sources are introduced, which have been explained as fungal poisoning, ergotism, or mass psychosis in the past.
CRIS-Team WoS Importer:2022-01-14

„Prächtiges Menschenmaterial“ – Anthropometrische Konstitutionsforschung auf der Suche nach dem statistischen Normalkörper (1914–1922) - Metzger, Nadine (NTM Zeitschrift für Geschichte der Wissenschaften, Technik und Medizin, 2020)
At the center of this work stands the anthropometric research program during World War I for studying constitutional medicine and the connected series of investigations by the medical internists Theodor Brugsch, Hermann Rautmann and Max Berliner, their advances in the statistics of variability as well as the subsequent debate in constitutional medicine and pathology on the definition of the physical norm. In order to create a data basis for the “normal” body in the study of constitutional medicine, a series of young German internists undertook comprehensive anthropometric studies in the context of World War I, thereby taking advantage of the opportunity offered them by war to conduct a series of examinations of soldiers, but without having first reflected on methods of measurement, comparison, and evaluation. At the same time, the concept of the “normal” body, then only vaguely formed, still needed to be critically expounded. However, this changed during the subsequent period and led not only to a stronger emphasis on methodology, rather also to greater competency in mathematical statistics and philosophical cogitation on the meaning of the “norm”. In this way, constitutional medicine originated the potent medical norm debate of the early 1920s which still resonates in medical theory today. By this means the few years following the end of World War I not only represented a turning point for constitutional medicine regarding the reflective use of methodology, but also introduced a new orientation of their research questions: away from the “normal” body to individuality.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Constitutional medicine; Hermann Rautmann; Max Berliner; Medical norm; Medical statistics; Theodor Brugsch